A REVIEW OF INDUSTRIAL 4.0 TECHNOLOGIES AND THEIR APPLICATION TO MANUFACTURING SUSTAINABILITY (International Journal of Food and Nutritional Sciences, 2022)
Despite being a relatively recently developed concept in business and marketing, sustainable marketing is already altering the rules. Sustainable marketing aims to satisfy the wants of the current generation without destroying the future and is based on social and environmental sustainability concepts. This is achieved through Industry 4.0, which is revolutionizing marketing and businesses across the globe. Recent advancements in automation and manufacturing techniques have led to Industry 4.0. Data management, industrial competitiveness, manufacturing processes, and efficiency can all be categorized under the umbrella term "industry 4.0." A few crucial supporting technologies mentioned in the "Industry 4.0" movement include digital twins, artificial intelligence, the Internet of Things (IoT), and cyber-security systems.